Principles of Corporate financial accounting - Reeve, James M., 1953-; Warren, Carl S.; Fess, Philip E. (Mason, OH : South-Western/Cengage Learning, 2008)
This textbook is HORRIBLE! I usually frown on using such harsh language for reviews, but this truly deserves it. Some people, and I trust that these people are indeed RARE individuals, may find the new examples helpful but they are not. This textbook fails in the area most critical to success, in that it does NOT succeed in approaching the subjects from a students perspective. It is extremely difficult to learn from this text because the examples in it are SO numerous that your though process is interuptted every 30 seconds with some illustrative example. I find these examples mostly to be unnecessary with a solid lecturer. Perhaps CENGAGE should have considered placing all the examples in one section and referencing them instead, but the fact remains that the learning process is disrupted often by unnecessary examples and illustrations.
Introduction to Accounting and Business -- Analyzing Transactions -- The Adjusting Process -- Completing the Accounting Cycle -- Accounting for Merchandising Businesses -- Inventories -- Sarbanes Oxley, Internal Controls, & Cash -- Receivables -- Fixed Assets and Intangible Assets -- Current Liabilities & Payroll -- Corporations: Organization, Capital Stock Transactions, and Dividends -- Long-Term Liabilities: Bonds and Notes -- Investments and Fair Value Accounting Complete Financial Statements for Mornin' Joe -- Statement of Cash Flows -- Financial Statement Analysis. Appendix A: Interest Tables. Appendix B: Reversing Entries. Appendix C: Special Journals and Subsidiary Ledgers Appendix D: Merchandising End-of-Period Spreadsheet. Appendix E: Annual Report. Appendix F: International Financial Reporting Standards to the TOC.
Includes bibliographical references and indexes.
1
Keywords: Corporations -- Accounting; Managerial accounting; Analyzing Transactions; Adjusting Process; Completing the Accounting Cycle; Accounting for Merchandising Businesses; Fixed Assets and Intangible Assets; Investments and Fair Value Accounting; Financial Statement Analysis